Prediksi Penyakit Gagal Jantung Tahun 2025-2028 Rawat Inap di RSUD Gambiran Kota Kediri - Anisa Rahmawati; Krisnita Dwi Jayanti; Eva Firdayanti Bisono; Ayu Pangestuti; Nugroho Nugroho; Nurhadi Nurhadi; Budi Pranoto (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Heart failure is the most common cardiovascular disease. Gambiran Regional Hospital has the 1st position of heart failure cases out of the top 10 diseases with the largest population in hospitalizations. To determine the prediction of heart failure disease in 2025-2028 which will increase or decrease. Using a descriptive research method, with a retrospective study research approach The population of all heart failure patients in 2021-2024 at Gambiran Regional Hospital, with a sampling technique of total sampling, the number of samples of inpatient heart failure patients in 2021-2024 at Gambiran Regional Hospital. Data collection was carried out by observation. The total number of heart failure patients increased significantly to 259 (2022). The trend has increased and decreased, the number of male patients jumped sharply to 150,3 (2024), while for women it jumped to 92,3 (2024). Overall, the prediction of the highest heart failure patient in 2028 will reach 316,2 while the lowest will be in 2025. The number of heart failure hospitalizations shows a trend of change that tends to increase during 2021–2024. Based on gender, male patients dominated visits. The 2025–2028 prediction predicts an increase in the number of patients, with the highest number in male patients and total visits reaching 316,2.: Hospitals can collaborate with local health departments to hold routine screening programs for those at high risk.